Optimized design of impulse turbines in the micro-hydro sector concerning air detrainment processes. (15th December 2015) - Kramer, Matthias; Terheiden, Kristina; Wieprecht, Silke
Abstract: Impulse turbines with tailwater depression are an efficient choice for energy recovery in drinking water systems. To reduce negative effects of detrained air downstream of the turbine casing, such as corrosion and reduced transport capacity, main processes and possible reduction of air detrainment have been investigated in detailed experimental studies on a micro-hydro Pelton machine with tailwater depression. The experimental setup has been designed to distinguish between dissolved and undissolved air detrainment. In case of dissolved air detrainment there is a clear relation between the amount of dissolved air and the counter pressure as well as the flow rate parameter. Experimental results for the amount of undissolved air detrainment show dependencies on geometrical dimensions, velocity coefficient, casing water level and the flow rate of the turbine. To avoid undissolved air detrainment, design equations are deducted for dimensioning the casing height and the casing diameter. Therefore the presented investigations show how air detrainment can be controlled or rather minimized by optimised casing-design of impulse turbines. Highlights: Experimental air detrainment measurements of a counter pressure Pelton turbine. Dissolved air detrainment depends on counter pressure and flow rate parameter. Undissolved detrainment increases with increasing flow and decreasing water level. Undissolved detrainment depends on geometrical dimensions and velocity coefficient. Development of design equations for dimensioning of cylindrical turbine casings.